Languishing: Do university students with better mental health literacy fare better? (Journal of Applied Learning and Teaching, 2025)
The term “languishing” gained widespread recognition and appeal during the COVID-19 pandemic as it succinctly captured the pervasive sense of stagnation, disconnection, and emotional depletion experienced by many individuals amidst prolonged uncertainty and isolation. While existing research on the topic of languishing during COVID-19 has largely focused on people’s mental health states in different populations and across different time periods, this paper elucidates if mental health literacy protects against languishing in higher education students—where languishing is reportedly most prevalent. In this study, we employed a correlational design and recruited participants from a university in Australia (N = 149). Our results indicated that mental health literacy did not predict languishing. With the COVID-19 pandemic underscoring the significance of mental health, our work contributes to the increasing emphasis on safeguarding and potentially enhancing mental well-being within both public and policy discourse.